Report of the Working Group on Housing for the North Eastern Region, Government of India Planning Commission - Planning Commission (Planning Commission, 1993)
In pursuance of the recommendations made in the Gangtok Housing Declaration and the Housing Finance Working Group, the Standing Committee on Housing Finance decided to set up a Working Group on Housing for the North Eastern Region. The Group was required to deliberate upon and recommend on the issues relating to the design of an appropriate Housing Finance System in keeping with the socio-economic conditions (particularly the land tenure system) and practices in the North Eastern Region; an assessment of the suitable local material based building technologies including measures for their popularisation and linkage with the lending norms; and the institutional set up for undertaking housing development activities in the Region (Paragraphs 1.1 to 1.3). The North Eastern States are characterised by difficult terrain, sparsely populated areas and inadequate physical infrastructure. The level of urbanisation is low as compared to the national average except in Mizoram (46.2%) and Manipur (27.7%). Even though homelessness as such is not the problem, there is a considerable need for upgradation of existing shelter and provision of adequate level of basic services. Despite considerable variation in housing forms and designs across the Region, there is a broad distinction of housing typologies and designs in rural and semi—urban areas and that in urban-areas.
Report of the Working Group on Housing for the North Eastern Region
Government of India